A 2-YEAR FOLLOW UP ON PM2.5 EXPOSURE AND COVID-19 MORBIDITY AND MORTALITY - Mace Firebaugh, Casey; Beeson, Tishra; Rich, Debra; Barrios, Yasmin Vivana; Wojtyna, Amie (Environmental Smoke, 2022)
Introduction: A previous study was conducted to examine the relationship between poor air quality in the form of PM2.5 exposure and COVID-19 morbidity and mortality in Yakima County, Washington (USA). Results showed there was a significant correlation (p<0.05) between PM2.5 exposure and COVID-19 hospitalization and mortality in the 12-day lag analysis, however it was not clear if this association remains consistent over time. The purpose of this study was to analyze a second year of PM2.5 exposure and COVID-19 morbidity and mortality in a population significantly impacted by poor air quality (PM2.5) and high COVID-19 morbidity to determine whether the findings of the previous study could be confirmed. Methods: A 12-day lag analysis correlating PM2.5 levels and county-level COVID-19 case counts, hospitalization, and mortality was conducted using Pearson correlation between the period of February 1, 2021 and December 20, 2021 in Yakima, County, Washington, USA. Results: PM2.5 was found to be significantly correlated (p<.011) to COVID-19 morbidity (r = 0.38), hospitalization (r = 0.41), and mortality (r = 0.18). Discussion: This study expands upon and confirm previous preliminary findings examining the association between poor air quality exposure and negative COVID-19 outcomes. Populations exposed to long-term PM2.5 may need additional safeguards from COVID-19 as they may have a higher risk of infection, hospitalization, and mortality.